A hungarikum termékeket fogyasztók életstílusának elemzése - Nótári, Mihály; Ferencz, Árpád (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The only products, which can meet the high demands of the Common Market are the ones which have added values and are in conformity with the quality and safety conditions of the food industry. Such products are what we consider ’Hungaricum’ and we have to do our best to improve our activities in order to find markets for them. Accordingly, we have made researches regarding the habits, preferences and lifestyle of customers, who purchase Hungarian products of gardening and food industry. There is no usable result in every case from marketing aspect given by the classical socio-demographic segmentation method. It is stated that consumers with analogous demographic situation purchase diverse products. The main motive of the deviation is the personal lifestyle. The lifestyle of consumers of horticultural and food industrial Hungaricums (typical Hungarian products) were examined and analyzed in the study.